The social sciences as an emerging global field. (September 2014) - Heilbron, Johan
Exploring the 'globalization' of the social sciences, this article first presents an historical interpretation of how transnational exchange in the social sciences has evolved. Earlier forms of international circulation are distinct from the more global arrangements that have emerged since the late twentieth century. Considering this globalizing field in more detail, it is argued that its predominant characteristic is a core–periphery structure, with a duopolistic Euro-American core, multiple semi-peripheries and a wide range of peripheries. Focusing on the global level, much of the existing research, however, has neglected the emergence of transnational regional structures. The formation of a transnational European field of social science is taken as an example of this process of transnational regionalization. The social sciences worldwide can thus be seen as a four-level structure. In addition to the local and national level, transnational regional as well as global structures have gained increasing importance and a better understanding of 'globalization' requires more precise studies of both levels, in their own right as well as in their evolving interconnectedness.